Socialization of Unmanned Aircraft Operation on Flight Safety in Palembang Airspace - Yuniar, Dwi Candra; Febiyanti, Herlina; Oka, I Gusti Agung Ayu Mas; Putra, Bambang Wijaya; Munir, M Syahrul (Graduate Program Magister Manajemen Pendidikan, 2024)
This socialization is carried out as a form of the application of the Tridharma of Higher Education, namely making research and compiling Scientific Journals within the Palembang Aviation Polytechnic. In addition, the purpose of this activity is to increase the knowledge and awareness of the people living around Sultan Mahmud Badaruddin II Airport Palembang. This activity aims to inform how to operate unmanned aircraft around the airport area, how safe distance is needed and what permits need to be made when operating unmanned aircraft. This activity was made based on reports from several pilots to the Air Traffic Controller about the many obstacles such as kites, drones, hot air balloons and as in Palembang airspace. The method used in this community service activity is the participatory method. So that the results are expected so that participants know the results of socialization related to how to operate unmanned aircraft that do not endanger flights. Then the results of the socialization were published on the social media of Palembang Poltekbang.